Navigating change: the ongoing efforts to contain poliovirus in the United States - Ottendorfer, Christy; Haynes Smith, Lia; Jorgensen, Shelley (Frontiers in Bioengineering and Biotechnology, 2026)
United States (U.S.) poliovirus research and vaccination programs have eliminated polio in the U.S. and brought the world to the brink of polio eradication. As part of a global action plan, the U.S. committed to safeguard the polio eradication efforts through identification of domestic facilities holding poliovirus materials and implementing stringent laboratory biocontainment measures overseen by U.S. CDC. In January 2025, the White House announced the withdrawal of the U.S. from the WHO. Consistent with the administration’s policy and guidance, the U.S. CDC is developing a new framework for poliovirus containment independent of WHO to protect the health security of the U.S. from the continued threat of poliovirus and ensure the long-term success of polio eradication.